The role of Deep Transcranial Magnetic Stimulation in Depression- a systematic review - Guilherme Matos de Almeida Bento Junqueira (2022)
ABSTRACT Background: Depression is considered as a condition of extremely high prevalence which very often brings an enormous burden to patients. Current ways of treatment frequently fail to decrease depressive symptoms and are also associated with high levels of toxicity. There is a need for new alternative treatments aiming to improve the health of these treatment-resistant patients. DTMS (deep transcranial magnetic stimulation) arises itself as a new type of treatment with a potential which is yet to be fully explored. Methods: Two authors conducted a systematic literature search through three different databases. Articles that assessed the effects of dTMS in patients suffering from unipolar or bipolar depression through the Hamilton Depression Rating Scale were included. Main outcomes were HDRS score changes and rates of response, remission and adverse effects. Results: Almost every included study showed that dTMS had a significant effect in reducing depressive symptoms, with high rates of response and remission and a scarce number of adverse effects registered. Limitations: Most of our included studies were uncontrolled and had a low number of participants. In addition to that, follow-up periods were short considering depression is a chronic and relapsing disease. Conclusions: Our results show that dTMS has the potential to become an important tool for treatment-resistant depression in the future, with high rates of response and an overall high degree of safety. However, further studies with a higher number of involved patients are required in order to fully establish the clinical utility of this new form of treatment.